Learning natural objects: A cognitive artifact of the way we were? - Vranić, Andrea (2009)
Experimental approach has proven useful in suggesting that human predisposition to learn basic aspects of hunting might be an evolutionary holdover from our pre-agricultural past. Recently, Sharps et al. (2002) showed that better recall of animal tracks is due to the human predisposition to effectively learn animal tracks due to their significance in the hunter-gatherer society. This experiment provides a further support of these findings. The rate of learning paradigm was employed to test the recall of picture-pseudoname pairs in three categories: animal tracks, berries (both due to the proposed cognitive adaptation) and feathers (natural control items). Using the repeated measures design, long-term retention was tested after 48 hours. The results showed a significant category x sex of participant interaction (F (2, 29) = 5, 004, p<.05). Further analysis showed female participants’ better retention of item-pseudonames pairs in the berries category and male participants’ better retention in the category of animal tracks. The results are interpreted from the evolutionary and cognitive psychology perspective.